2017
DOI: 10.1155/2017/1092838
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management of Calcareous Saline-Sodic Soil in Arid Environments: The Leaching Process in the Jordan Valley

Abstract: A leaching experiment of calcareous saline-sodic soil was conducted in Jordan Valley and aimed to reduce the soil salinity ≤ 4.0 dS m −1 . The quantification of salt removal from the effective root zone was done using three treatment scenarios. Treatment A contained soil amended with gypsum leaching with fresh water (EC = 1.1 dS m −1 ). Treatments B and C contained nonamended soil, but B was leached with fresh water only while treatment C's soil was washed with saline agricultural drainage water (EC = 8 dS m −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
2
10
0
5
Order By: Relevance
“…Wang, Bai, and Yang () also reported that Ca ions supplemented through by‐products of flue gas desulfurisation assisted in the reduction of soil BD by promoting formation of soil aggregates. The improvement in the properties of sodic soil with the addition of GR, FA, and GM did influence and minimise soil ESP and decrease pH as also noted by the previous studies (Batarseh, ; Ors et al, ; Shirale, Kharche, Zadode, Meena, & Rajendiran, ). The reason for decrease in soil pH in our study is attributed to iron and aluminium sesquioxides contained in feed coal (Kutchko & Kim, ; Moreno et al, ) that hydrolyse to form ionisable acids.…”
Section: Discussionsupporting
confidence: 78%
“…Wang, Bai, and Yang () also reported that Ca ions supplemented through by‐products of flue gas desulfurisation assisted in the reduction of soil BD by promoting formation of soil aggregates. The improvement in the properties of sodic soil with the addition of GR, FA, and GM did influence and minimise soil ESP and decrease pH as also noted by the previous studies (Batarseh, ; Ors et al, ; Shirale, Kharche, Zadode, Meena, & Rajendiran, ). The reason for decrease in soil pH in our study is attributed to iron and aluminium sesquioxides contained in feed coal (Kutchko & Kim, ; Moreno et al, ) that hydrolyse to form ionisable acids.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies showed that rhizobacteria isolated from plants grown in arid and semi-arid areas are often adapted to adverse detrimental conditions and have the potential to promote plant growth under various environmental stresses (Ashraf et al, 2010;Dodd and Perez-Alfocea et al, 2012). Biological methods, such as salt-tolerant plants and microbial bacterial strains, were reported to be effective in reclaiming salt-affected areas (Batarseh, 2017). The use of green manure crops such as salt-tolerant legumes as an alternative strategy to reclaim saline soils results in increase adsorption capacity and nutrient availability, and improved soil physico-chemical properties (Ashraf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of ITD2 increased the buffering capacity of the coastal sandy soil so that the K + leaching decreased. The use of tapioca dregs also offers environmental advantages by reducing (+) indicates there is an interaction effect; the values in the same column with the same letter are not significantly different at P < 0.05; the mean followed by the same superscript letters are not significantly different according to the orthogonal contrast at P < 0.05; SC -soil conditioner; I -Inceptisol; V -Vertisol; T1 -tapioca 1%; T2 -tapioca 2%; TD1 -tapioca dregs 1%; TD2 -tapioca dregs 2%; P1 -PVA 0.1%; P2 -PVA 0.2%; C -control; initial Ca 2+ = Ca 2+ derived from sandy soil+clay+polymers; residual Ca 2+ = initial Ca 2+ -leached Ca 2+ +) or (-) indicates there is an interaction or no interaction effect; the values in the same column with the same letter are not significantly different at P < 0.05; the Mean followed by the same superscript letters are not significantly different according to orthogonal contrast at P < 0.05; SC -soil conditioner; I -Inceptisol; V -Vertisol; T1 -tapioca 1%; T2 -tapioca 2%; TD1 -tapioca dregs 1%; TD2 -tapioca dregs 2%; P1 -PVA 0.1%; P2 -PVA 0.2%; (Jones et al 2012;Mahmoodabadi et al 2013;Zhang et al 2015;Batarseh 2017). The high mobility causes Na + to be easily carried away by the movement of the vertical water flow (Mahmoodabadi et al 2013;Wang et al 2016).…”
Section: Resultsmentioning
confidence: 99%